NATURAL MATERIALS FOR PROTECTING ICE AND COMPACTED SNOW. - Stehle, Nancy S. (1967)
In much of the polar regions, many facilities are constructed on ice and permanent snowfields. During the summer, high solar radiation and near - or above thawing temperatures decrease the wear resistance of ice and snow surfaces. Tests were conducted on the ability of sawdust, snow, and chipped-ice coverings to protect ice from melting and deterioration due to high solar radiation and near- and above-thawing temperatures; these results were compared with the results of other similar tests performed with urethane foam. It was concluded that field situations in which the air temperature is not above freezing for long periods of time but solar radiation is high, chipped-ice and snow covers 3 inches thick or more can be used as effectively as 1/4 inch of sawdust or a 1/4-inch slab of flexible urethane foam to protect ice surfaces. In similar field situations where the air temperature is above freezing for extended periods of time, however, 1-inch-thick covers of rigid urethane foam in slab or granule form should be used. (Author)